Psychosocial employment characteristics and postpartum maternal mental health symptoms. Issue 1 (17th October 2016) - Schwab‐Reese, Laura M.; Ramirez, Marizen; Ashida, Sato; Peek‐Asa, Corinne
Abstract: Introduction: For new mothers returning to work, the role of the workplace psychosocial environment on maternal mental health has not been fully described. Objectives: The purpose of this study was to identify the relationship between psychosocial employment characteristics and mothers' postpartum depression, anxiety, and stress symptoms. Methods: Ninety‐seven women answered survey questions regarding employment, job demand, control, and support, and postpartum depression, anxiety, and stress symptoms soon after live birth and 6 months later. Results: Working and nonworking mothers reported similar mental health symptoms. Psychological characteristics of employment were not associated with increased odds of mental health symptoms. Increased social support provided by coworkers, supervisors, and the organization was associated with reduced odds of anxiety symptoms. Conclusion: Our findings identified lack of workplace social support as a modifiable risk factor for postpartum anxiety. Future evaluations of workplace social support interventions may be explored to improve postpartum mental health symptoms. Am. J. Ind. Med. 60:109–120, 2017. © 2016 Wiley Periodicals, Inc.